ANALISIS PENGARUH DAUN GAMAL (Gliricida sepium) DAN DAUN PISANG PADA PROSES PERCEPATAN PEMATANGAN TERHADAP MUTU BUAH PISANG CAVENDISH (Musa acuminata Cavendish) - Ifmalinda, Ifmalinda; Mutiara Helmi, Annisa; Andasuryani (Jurnal Teknologi Pertanian Andalas, 2025)
Cavendish bananas have great potential and are widely cultivated and consumed by the community, both processed and raw. A good banana is a banana that is ripe while it is still on the tree, but many farmers pick the bananas when they are not ripe. The harvested fruit will ripen without ripening with uneven ripeness and the resulting color is not attractive, therefore ripening is carried out. The ripening materials used are gamal leaves and banana leaves because it contains ethylene which functions in the fruit ripening process and is free from chemicals. The purpose of this study was to determine and analyze the best type of ripening material for the quality of Cavendish Banana (Musa acuminata Cavendish). The method used was the Completely Randomized Design experimental method with 1 factor, namely the type of ripening material such as gamal leaves and banana leaves. The ratio of gamal leaves used was 30%, 40%, and 50%, while the ratio of banana leaves was 30%, 40%, and 50%. Based on the results of the study, the ripening material had a significant effect on the quality of Cavendish Bananas. The ratio of gamal leaves of 50% is the best ripening material for the quality of Cavendish Bananas with a weight loss value of 1.035%, hardness of 31.328 (N/cm2), total dissolved solids of 12.936°Brix, water content of 71.674%, color (light) of 22.661, and color (hue) of 37.934.